Andrew Jackson - Marchant-Shapiro, Theresa (Hatred of America's Presidents: Personal Attacks on the White House from Washington to Trump, 2018)
This work examines expressions of personal hostility and animosity toward presidents―even beloved ones―throughout American history and their impact on policymaking, politics, and culture.• Investigates a unique form of expressions of hatred toward American presidents, focusing on the personal rather than the political• Covers every president from Washington to Trump• Includes coverage of personal attacks on First Families• Details how presidents and allies responded to these attacks
Keywords: dept.psc